Model Manajemen Terpadu Pertanian Hortikultura Organik pada Lahan Sempit - Suryadi, Dede; Megawati, Ayuningtyas; Susilo, Buana; Dalimartha, Lengga Nurullah; Wiguna, Eko Chandra; Isdiantoni, Isdiantoni; Koentjoro, Maharani Pertiwi; Prasetiyo, Endry Nugroho (Universitas Sebelas Maret, 2017)
Integrated management of organic farming is an agriculture management system with an effort in developing the organic basis of cropping system to improve soil health, and pest & disease controlling to achieve sustainable productivity. Integrated management model of organic horticulture can be done alternatively on narrow land thereby intercropping and companion of several crops in order to improve yield. For instance, planting of different plants families such as herbs & flower in one area such as kenikir and tagetes to reduce the population of pest and to improve natural enemies population.